Designing embedded systems with PIC microcontrollers - Wilmshurst, Tim (Newnes, 2010)
Includes bibliographical references and index; Section 1. Getting started with embedded systems -- section 2. Minimum systems and the PIC 16F84A -- section 3. Larger systems and the PIC 16F873A -- section 4. Smarter systems and the PIC 18F2420 -- section 5. Where can we go from here? : distributed systems, bigger systems